A semi-supervised approach for predicting cell-type specific functional consequences of non-coding variation using MPRAs - Zihuai He (Nature Portfolio, 2018)
Predicting the functional consequences of non-coding genetic variants is a challenge. Here, He et al. present GenoNet, a semi-supervised method that combines information from experimentally confirmed regulatory variants with cell type- and tissue specific annotation for function prediction.